Impact of Grassland Reseeding, Herbicide Spraying and Ploughing on Diversity and Abundance of Soil Arthropods - Liu, Wei; Zhang, Junling; Norris, Stuart L.; Murray, Philip J. (Frontiers in Plant Science, 2016)
In order to determine the interactive effect of reseeding, herbicide spraying and ploughing on soil fauna communities, we conducted a grassland reseeding experiment combined with pre-reseed management to examine how with the whole reseeding process affects soil faunal composition. Sampling occasions and exact treatments were as follows: 1) before chemical herbicide spray; 2) after spray but before ploughing; 3) after ploughing but before reseeding; and 4) after one year of recovery. Our results demonstrate that, Acari and Collembola were the two soil fauna taxa with the highest abundance and accounted for around 96% of the relative total abundance among the various managements. Herbicide application tended to increase soil invertebrate abundance. Conversely, subsequent ploughing significantly reduced soil invertebrate abundance and had an obvious negative effect on soil primary and secondary decomposers, which were mainly due to the variations of Acari (especially Oribatida) and Coleoptera group abundance. Moreover, reseeding also reduced the individual number of the groups mentioned above, and favoured those predators with a larger body size and individual weight. After one year recovery, Collembola abundance recovered to the pre-treatment levels, while with Arthropod and Acari groups were still fluctuating.